Dampak Covid-19 Terhadap Harga Saham dan Kinerja Keuangan Perusahaan - Annisa Nadiyah Rahmani (Universitas Islam Bandung, 2020)
The purpose of this study to determine the impact of Covid-19 on stock prices and financial performance of companies on LQ-45 issuers listed on the IDX. This study examines the impact of Covid-19 on stock prices and financial performance before being exposed to Covid-19 for Q3 2019 and after being exposed to Covid-19 for Q1 2020. Stock prices are measured using closing stock prices and financial performance is measured using a ratio formula that is Return on Assets (ROA), Operating Profit Margin (OPM), and Net Profit Margin (NPM). This study uses a sample of LQ-45 companies that have published their financial statements on the Indonesia Stock Exchange (IDX). This research uses multiple linear regression methods using SPSS 25. The results of this study indicate that (a) Pandemic Covid-19 has an impact on stock prices and (b) Pandemic Covid-19 has an impact on financial performance.